(untitled) (Journal of Bio-Science, 2021)
The present study estimated the concentration (in ppm) of heavy metals of Zn, Fe, Cu and Pb in water samples and edible tissue of Labeo boga; both collected from the non polluted (Station I) and polluted (Station II) locations of river Tawi, Jammu, India. The mean concentration of heavy metals (Zn, Fe, Cu, Pb) at Station I were 0.048±0.008 (ppm); 0.016±0.001 (ppm); 0.157±0.002 (ppm) and 0.0001±0.0001 respectively; while at Station II, these values were 0.133±0.001 (ppm); 0.022±0.002 (ppm); 0.206±0.002 (ppm) and 0.002±0.001 (ppm) respectively; the statistical difference between the stations were significantly higher (p<0.05). The order of heavy metal load obtained in water samples at both the stations was found to be Fe>Zn>Cu>Pb. Also, the mean bioaccumulation of heavy metals viz. Zn, Fe, Cu and Pb in the edible tissue of fish at Station I was found to be 0.374±0.011 (ppm), 0.105±0.02 (ppm); 0.094±0.04 (ppm) and0.001±0.0001 (ppm) respectively; on the other hand, mean bioaccumulation was 0.539±0.013 (ppm); 0.156±0.04 (ppm); 0.121±0.023 (ppm) and 0.0013±0.0001 (ppm) respectively at Station II. Even though bioaccumulation of the heavy metals in the experimental sites did not exceed the acceptable limits recommended by the agencies like FAO and WHO, the present results showed an increasing trend of the accumulation, which definitely poses a serious threat to the survival of aquatic organisms in the study area. J. Bio-Sci. 29(2): 19-29, 2021 (December)